Mobile phone usage and consumption motivations in Ota, Nigeria (2010)
Studies in mobile telephony have shown their relevance for African development but little is known about the usage patterns and consumption motivations of different groups in Nigeria. The study examined the phenomenon among University staff and students in Ota, with a view to describing the consumption motivations and patterns of mobile phone use. Survey, focus group discussions (FGDs) and in-depth interviews (IDIs) were used to generate data that explained the study problem. While the quantitative approach highlighted the usage patterns, qualitative methods described the factors that motivate mobile consumption. Findings show that mobile phones are mostly used for oral communication and social networking by adults and youths, respectively. Usage is predicated on the need for information, accessibility, connectivity, interactivity, networking, entertainment and cost efficiency while consumption is motivated by economic incentives, social benefits and convenience of use. Because mobiles navigate sociocultural, economic and spatial boundaries, they provide a ready platform for the dissemination of development messages in Nigeria and point to the need for more attention in explaining the behavioural aspects of mobile technology in the developing countries of sub-Saharan Africa.